Report of the Planning Group on Civil Aviation at the Turn of the Century - Planning Commission (Planning Commission, 1986)
Later on, Dr. N. K. Sengupta, Director General Tourism, Government of India, was also included as a member of the Group in order to ensure that projections and plans for future traffic growth both on the International and domestic sector are made in full consultation and in harmony with the Department of Tourism. Also, in its first meeting held on the 7th/8th January, 1986, the Group felt that since there was considerable coordination required between the civil and defence agencies in the management of airspace, provision of facilities at civil as well as military airports, release of pilots from the Indian Air Force for civil aviation, etc., it would be useful to co-opt a member from the Indian Air Force.
Planning Commission
Planning Commission